Iron and cancer: overview of the evidence from population-based studies - Zeidan, Rola S.; Yoon, Hyung-Suk; Yang, Jae Jeong; Sobh, Amin; Braithwaite, Dejana; Mankowski, Robert; Leeuwenburgh, Christian; Anton, Stephen (Frontiers in Oncology, 2024)
Iron is an essential nutrient required for various physiological processes in the body. However, iron imbalance can potentially contribute to initiating and promoting cancer development. Epidemiological studies have investigated the relationship between dietary iron intake and the risk of different types of cancer, yet, not all studies have consistently shown a significant association between dietary iron and cancer risk. Also, studies have shown different effects of dietary heme and non-heme iron intake on cancer risk. While some epidemiological studies suggest a possible link between high dietary iron (mainly heme-iron) intake and increased cancer risk, the evidence remains inconsistent. Moreover, multiple iron biomarkers, which can mirror physiological iron status, have demonstrated varied correlations with the risk of cancer, contingent upon the specific biomarker analyzed and the type of cancer being investigated. Here, we have investigated the current evidence on the potential relationship between dietary iron intake on one hand, and iron biomarkers on the other hand, with the risk of developing different types of cancer, including breast, prostate, lung, pancreatic, colon, colorectal, and liver cancers. Further research is warranted to better understand the complex relationship between dietary iron, physiological iron and cancer development. Future research should account for factors that affect and interact with dietary iron and physiological iron levels, such as genetic susceptibility, overall diet quality, and lifestyle habits.